Analysis of Factors Affecting Stock Prices of Companies in the Agricultural Sector - Nugra Irianta Denashurya (Dinasti Review, 2025)
This study aims to analyze the factors that influence stock prices of companies in the agricultural sector listed on the Indonesia Stock Exchange during the 2012–2016 period. The research examines both fundamental and macroeconomic factors, including Return on Assets (ROA), Price Earning Ratio (PER), Debt to Equity Ratio (DER), Earning Per Share (EPS), exchange rate, and world oil prices. Using a descriptive quantitative approach with panel data regression analyzed through EViews 6, the study investigates the extent to which these variables affect stock price movements. The results show that ROA, PER, and EPS have a positive and significant effect on stock prices, indicating that better profitability and earnings performance contribute to higher market valuation. Meanwhile, DER and world oil prices negatively affect stock prices, suggesting that higher leverage and increasing oil prices reduce investor confidence. The exchange rate shows a positive influence, implying that currency appreciation enhances stock price performance. The findings provide useful insights for investors and policymakers to understand financial and external factors influencing agricultural stock behavior in Indonesia.